Primary biliary cirrhosis and psoriasis: a two-sample Mendelian randomization study - Zhao, Diqian; Zhao, Qinyu; Xu, Fangwei; Zhang, Fang; Bai, Wenzhe (Frontiers in Immunology, 2024)
Background: Primary biliary cirrhosis (PBC) and psoriasis are frequently observed to co-occur in clinical settings. However, the causal associations and underlying mechanisms between PBC and psoriasis remain poorly defined.In this study, we conducted bidirectional MR analysis to explore the causal relationship between PBC and psoriasis using four MR methods: inverse-variance weighted, MR-Egger regression, weighted median, and weighted mode. Sensitivity analyses were carried out, employing different models and testing methods for comparison to assess the influence of heterogeneity and pleiotropy on our findings and to confirm the robustness of these results.A causal relationship between the risk of PBC and psoriasis was identified, as confirmed by IVW analysis (OR: 1.081, 95%CI: 1.028~1.137, P<0.05). The other three MR methods also produced similar results. However, psoriasis did not have a causal effect on PBC risk (OR: 1.022, 95%CI: 0.935~1.118, P>0.05). The intercept of MR-Egger regression was 0.0013 (P>0.05), This is a provisional file, not the final typeset article indicating that genetic pleiotropy did not influence the results. Additionally, the leave-one-out analysis demonstrated the robustness of our MR findings.This study reveals a causal relationship between PBC and psoriasis, with PBC increasing the risk of psoriasis, but not the reverse. This potential causal relationship offers a new perspective on the etiology of PBC.